KBELA: O cabelo e a mulher negra no cinema contemporâneo brasileiro - Rosário, Lílian Valéria Cunha do (2019)
The present research discusses the hair and the black woman out of the short film Kbela (2015), directed and scripted by Yasmin Thayná. Through the black presence inside the first national cinemas to the contemporary cinema, with the theoretical help of Noel dos Santos Carvalho, this research analyses genre and race of black filmmakers in brazillians black cinema. The curly hair in Yasmin Thayna's work is perceived as a black specificity, since negroid traits are important racial markers in the lives of black women. The more distant from the Eurocentric pattern of beauty, the more susceptible are to institutional and everyday racism, bell hooks helps us understand how the non-acceptance of curly hair affects the self-esteem of black women. The film Kbela will investigate the presence of the black body in capillary transition. According to director Yasmin Thayná, the film is divided into three parts: oppression, ritual, celebration. Through these images and other works performed by black women, we will understand this new look and, therefore, new forms of black representation in the arts and contemporary cinema.